IMPACT OF THE AVAILABILITY OF HOST PLANTS AND PREY APHIDS ON THE OCCURRENCE OF LADY BEETLES IN WESTERN U.P. - ., INDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
The lady beetle and its developmental stages are dependent on the availability of the aphid food, which may only grow, when the specific food crop is available in the field. Thus, in nature a very regular and specific change and their interrelationship among host plants, aphid pests and the predator Coccinella septempunctata Linn. exist during mid July to April due to prevailing suitable condition in Saharanpur (the specific area of the work). Simultaneous, occurrence of the host plants in the field is a bio-indicator of the seasonal prevalence of the notorious aphid pests and predatory lady beetle population, depending on the suitability of the climatic condition. Thus, the growth of the host plant in the field indicate appearance of aphids which act as prey for the predator C. septempunctata.